Endomyocardial Fibrosis Secondary to Chronic Eosinophilic Leukemia: Case Report - Tourinho Delmondes Trindade, Yasmin; Oliveira Bastos , Caio; Garcez da Cruz , Mariana; Maria Delmondes Freitas Trindade, Leda; Flávio Galvão Gonçalves , Luiz; Augusto Soares Barreto Filho, José; dos Santos Barros Campos, Milena (International Journal of Medical Science and Clinical Research Studies, 2024)
Endomyocardial fibrosis (EMF) is characterized by fibrosis of the endomyocardium of one or both ventricles and atrioventricular valves. Progressive fibrosis leads to irreversible restrictive cardiomyopathy, progressing to heart failure (HF), thromboembolic phenomena, and arrhythmias. It is one of the main complications of chronic eosinophilic leukemia (CEL), resulting from intense eosinophilic infiltration into cardiac tissue. This case is of a 34-year-old male patient with past medical history of CEL, who developed EMF and severe heart failure, NYHA (New York Heart Association) IV, and underwent endocardectomy and mitral and tricuspid valvuloplasty. After the procedure, he improved to NYHA II, initiated cardiovascular rehabilitation, and returned to daily activities.